2018
DOI: 10.1186/s40104-018-0257-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of indirect calorimetry and metabolomics profiling reveals alterations in energy metabolism between fed and fasted pigs

Abstract: BackgroundFasting is a simple metabolic strategy that is used to estimate the maintenance energy requirement where the energy supply for basic physiological functions is provided by the mobilization of body reserves. However, the underlying metabolic components of maintenance energy expenditure are not clear. This study investigated the differences in heat production (HP), respiratory quotient (RQ) and plasma metabolites in pigs in the fed and fasted state, using the techniques of indirect calorimetry and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
1
17
1
Order By: Relevance
“…These compounds were then imported into the module of pathway analysis in Metaboanalyst 3.0 (https://www.metaboanalyst.ca/MetaboAnalyst/ upload/PathUploadView.xhtml) to generate the pathway topology analysis. The metabolic pathway with an impact value greater than 0.1 was characterized as the significantly relevant pathway [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds were then imported into the module of pathway analysis in Metaboanalyst 3.0 (https://www.metaboanalyst.ca/MetaboAnalyst/ upload/PathUploadView.xhtml) to generate the pathway topology analysis. The metabolic pathway with an impact value greater than 0.1 was characterized as the significantly relevant pathway [18].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples from pigs kept at the ambient temperatures of 18 • C, 23 • C and 32 • C (defined as low, neutral, and high ambient temperature group, respectively) were used for non-target metabolomics profiling assay, followed the procedures described by Liu et al (2018) with some modifications [18].…”
Section: Non-target Metabolomics Profiling In Plasma and Data Analysismentioning
confidence: 99%
“…Interestingly, sows with excessive weight loss had a higher level of plasma betaine in this study. Similarly, a previous study has shown an increase of betaine observed in growing pigs at 48 h after fasting [12]. Betaine, of dietary origin or produced from choline, is the methyl donor in methionine regeneration from homocysteine [44].…”
Section: Amino Acids Metabolism-relatedmentioning
confidence: 55%
“…Moreover, the level of tyrosine was significantly upregulated in HWL sows. Tyrosine, as a potent ketogenic amino acid [38], can be transformed into ketone bodies in the liver and contribute as a fuel during nutritional restriction [12]. The increased tyrosine concentration may partly be explained by tyrosine acting as a ketogenic amino acid to meet the energy requirements of lactating sows with lower feed intake.…”
Section: Amino Acids Metabolism-relatedmentioning
confidence: 99%
“…Those compounds were then imported into the module of pathway analysis in Metaboanalyst 3.0 (https://www.metaboanalyst.ca/MetaboAnalyst/upload/PathUploadView.xhtml) to generate the pathway topology analysis. The metabolic pathway with impact value greater than 0.1 was characterized as the signi cantly relevant pathway [19].…”
Section: Discussionmentioning
confidence: 99%